2011
DOI: 10.3390/membranes1040354
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Transmembrane RING Finger Proteins in Cellular and Organelle Function

Abstract: A large number of RING finger (RNF) proteins are present in eukaryotic cells and the majority of them are believed to act as E3 ubiquitin ligases. In humans, 49 RNF proteins are predicted to contain transmembrane domains, several of which are specifically localized to membrane compartments in the secretory and endocytic pathways, as well as to mitochondria and peroxisomes. They are thought to be molecular regulators of the organization and integrity of the functions and dynamic architecture of cellular membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
76
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 254 publications
(349 reference statements)
0
76
0
7
Order By: Relevance
“…Among the RBR ubiquitin ligase family, there are five TMcontaining RBR proteins, including RNF19A (also named Dorfin), RNF19B (also named IBRDC3), RNF144A, RNF144B (also named IBRDC2 or p53RFP), and RNF217 (also named IBRDC1) (35). It has been shown that RNF19A requires both RBR and the TM domain to form high molecular weight forms that may be autoubiquitinated RNF19A (36).…”
Section: Discussionmentioning
confidence: 99%
“…Among the RBR ubiquitin ligase family, there are five TMcontaining RBR proteins, including RNF19A (also named Dorfin), RNF19B (also named IBRDC3), RNF144A, RNF144B (also named IBRDC2 or p53RFP), and RNF217 (also named IBRDC1) (35). It has been shown that RNF19A requires both RBR and the TM domain to form high molecular weight forms that may be autoubiquitinated RNF19A (36).…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitylation of activated receptors is mediated by intracellular ubiquitin E3 ligases such as c-Cbl and Nedd4, although subsequent delivery steps are regulated by a series of ubiquitin-binding proteins [1,2]. cellular organelles and intracellular vesicles [4]. Of those, approximately 50 genes are predicted to encode transmembrane proteins, some of which show specific localization on intracellular membrane components, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The human genome harbours a large number of genes encoding ubiquitin E3 ligases (∼ 600 genes) [3], which mediate protein ubiquitylation to specific substrates. The PA-TM-RING family proteins are one subclass of the transmembrane-type ubiquitin ligases, and are composed of an N-terminal putative signal peptide, a PA (proteaseassociated) domain, a TM (transmembrane) domain, as well as a RING (really interesting new gene) domain [4,5]. cellular organelles and intracellular vesicles [4].…”
Section: Introductionmentioning
confidence: 99%
“…We propose that the Asi ubiquitin ligase targets such mislocalised and potentially harmful proteins for degradation. Although the Asi proteins are not obviously conserved outside of yeast, the general importance of membrane-associated protein degradation mechanisms and the large diversity of integral membrane RING domain proteins in mammalian cells 29 suggest that dedicated E3 ubiquitin ligases functioning in INM-associated protein degradation probably exist in higher eukaryotes.…”
mentioning
confidence: 99%